Evaluation of the Oxiris Membrane in Cardiogenic Shock Requiring Extracorporeal Membrane Oxygenation Support: Study Protocol for a Single Center, Single-Blind, Randomized Controlled Trial - Andrei, Stefan; Nguyen, Maxime; Berthoud, Vivien; Morgant, Marie-Catherine; Bouhemad, Belaid; Guinot, Pierre-Grégoire; , The ECMORIX Study Group; Martin, Audrey; Radhouani, Mohamed; Constandache, Tiberiu; Grosjean, Sandrine; Voizeux, Pierre; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is the rescue treatment proposed to patients with refractory cardiogenic shock. The VA-ECMO implantation promotes inflammation and ischemia-reperfusion injuries through the VA-ECMO flow, causing digestive mucosa barrier disrupture and inducing translocation of bacterial wall components - Lipopolysaccharides (LPS) with further inflammation and circulatory impairment. LPS is a well-studied surrogate indicator of bacterial translocation. Oxiris membrane is a promising and well-tolerated device that can specifically remove LPS. The main study aim is to compare the LPS elimination capacity of Oxiris membrane vs a non-absorbant classical renal replacement (RRT) membrane in patients with cardiogenic shock requiring VA-ECMO. Methods ECMORIX is a randomized, prospective, single-center, single-blind, parallel-group, controlled study. It compares the treatment with Oxiris membrane versus the standard continuous renal replacement therapy care in patients with cardiogenic shock support by peripheral VA-ECMO. 40 patients will be enrolled in both treatment groups. The primary endpoint is the value of LPS serum levels after 24 hours of treatment. LPS serum levels will be monitored during the first 72 hours of treatment, as clinical and cardiac ultrasound parameters, biological markers of inflammation and 30-day mortality. Discussion Oxiris membrane appears to be beneficial in controlling the VA-ECMO-induced ischemia-reperfusion inflammation by LPS removal. ECMORIX results will be of major importance in the management of severe cases requiring VA-ECMO and will bring pathophysiological insights about the LPS role in this context.